LITERATUR REVIEW : AKSESIBILITAS PELAYANAN FASILITAS PUBLIK BAGI PENYANDANG DISABILITAS TUNANETRA - Adelia Ayu Rama; Hastin Trustisari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Accessibility is a fundamental human right for all individuals, including those with disabilities. The Ministry of Public Works Decree No. 468/KPTS of 1998 emphasizes that accessibility is a facility provided to people with disabilities to ensure equal opportunities in all aspects of life. Accessibility is especially important for visually impaired individuals, who often face challenges in accessing public services. In Indonesia, the number of people with disabilities is not proportionate to the attention given by the government to the issues they face. This literature review is a narrative literature review. The purpose of this literature review is to explore the issue of accessibility to public facilities for visually impaired individuals. The results of the literature review show that the implementation of regulations and the rights of people with disabilities still face various challenges, particularly in ensuring adequate accessibility in public facilities. Although there are supportive regulations, their implementation is often suboptimal due to a lack of understanding and awareness among the public and government about the importance of accessibility and the protection of disability rights.